Adaptive thermal comfort model study for public buildings in urban area / Chew Bee Teng - Chew, Bee Teng (2012)
This thesis presents a comprehensive review of the literature of the Fanger’s PMV and adaptive thermal comfort models which were developed in different buildings and climates. Basically, the adaptive thermal comfort model is the correlation between the indoor neutral temperature and the outdoor temperature. An important premise of this thesis is the fact that the Fanger’s model underestimates the thermal impression in the actual case and thus the model is no longer valid for use in certain climates. As a consequence, many researchers have developed adaptive models from field studies for different climates and countries. However, there is still no adaptive model that can be applied in designing the airconditioning systems for different buildings in all countries with the tropical climates including Malaysia. Based on this comprehensive review, internationally recognized adaptive models are needed to achieve better thermal conditions in a variety of buildings such as hospitals, offices and lecture halls in the tropics. For hot and humid climates, the adaptive thermal comfort models were developed as part of this research by using the collected results from a large field study in the hospitals, office buildings and lecture halls. Field measurements were conducted in nine hospitals with feedbacks from 293 workers. The relationships between the operative temperature and the behavioural adaptations were determined in this research. In the developed adaptive model for hospitals, the acceptable indoor neutral temperatures lay within the range of 23.3 - 26.5oC, with the outdoor temperatures ranging between 25.4 - 35.0oC. The neutral temperature, which is the most comfortable temperature for the hospital workers, was 26.4oC. On the other hand, from the survey of the seven air-conditioned office buildings with 322 occupants, the acceptable indoor neutral temperatures found were within the range of 23.3 – 25.2oC, with the outdoor temperatures ranging between 21.1 - 35.4oC. The most comfortable temperature for office occupants was 24.1oC. Furthermore, based on the field measurement in six lecture halls with 178 students, the acceptable indoor neutral temperatures lay within the range of 23.9 - 26.0oC, with the outdoor temperatures ranging between 27.0 – 34.6oC. The neutral temperature found for students in the lecture hall was 25.7oC. Finally, the potential energy savings in the air-conditioning system was found to be 14.4 % for the hospitals, 0.6 % for the office buildings and 10.2 % for the lecture halls when increasing the temperature set point to the neutral temperature determined in the present research study.